A Randomized Controlled Field Trial: A Gamified Training Course on Workplace Health and Safety Prevention for Middle School Students – "Let's Play 81!" (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionInjury prevention and the promotion of health in the workplace are priority objectives starting from school age. Early and effective training can help develop a safety culture in future workers. However, traditional methods often fail to engage students. Gamification, the integration of game elements into educational contexts, has emerged as a promising strategy to increase engagement, improve learning, and enhance working memory [1-5].ObjectivesTo evaluate the effectiveness of the gamified training course "Let's Play 81!" (“Giochiamo a 81!”) in promoting and improving knowledge of workplace health and safety, in reference to the contents of Italian Legislative Decree 81/2008 [6], among middle school students.MethodsA teaching kit was created, consisting of a box (30×20×10 cm) containing an operational manual and the materials necessary for three different types of games: a role-playing game ("81 si gira!"), a board game ("Riduci il premio") and a card game ("Mettici la mano") [7]. The games were designed to reinforce the key concepts of Legislative Decree 81/2008, with particular attention to the duties and responsibilities of key figures in prevention (company owner, safety executive, operator in charge, Prevention and Protection Service Manager, security officer, inspector, occupational health physician, workers’ safety representative and a simple worker).The study was conducted following CONSORT guidelines [8]. The study was set in third-year classes from three middle schools of Rome. A 15-question quiz was administered to both the intervention group (IG) and the control group (CG) at the beginning (T0) and at the end of the training day (T1). "Score81" was calculated (range 0–15), based on the number of correct answers of the quiz. The quiz, validated in a previous study with an adult population (Cronbach’s α > 0.70), required one correct answer among four alternatives, including the "don’t know" option.The intervention included a 1-hour lecture, with materials (slides and theoretical content) available in the manual included in the kit, followed by 2.5 hours of playful-formative activities with the three games. Students were divided into groups of 7–9 participants, with about 40 minutes dedicated to each game. The activities were led by graduates in Prevention Techniques, specializing in Occupational Medicine, competent doctors, and university professors.The project received ethical approval from the Universitas Mercatorum Ethics Committee on March 13, 2025.Qualitative variables were described using absolute frequencies and percentages, while quantitative ones were described using means and standard deviation (SD). The comparison between IG and CG was performed using chi-square test for qualitative variables and independent t-test or Mann-Whitney test in the case of non-normality. The pre-post Score81 change was analyzed with paired t-tests or the equivalent non-parametric test. Normality was checked using skewness and kurtosis coefficients and the Kolmogorov-Smirnov test. The level of statistical significance was set at p 0.05).Based on the sample size obtained of both groups, it was possible to define the hypothesis of being able to observe a mean difference in the Score81 between CG and IG at time T1 of at least 3.96, with 80% power and a 95% level of significance, assuming SD=2.At the start of the study (T0), there were no significant differences in the Score81 between the groups (IG: 4.87 ± 2.41; CG: 4.69 ± 2.14; p=0.597). By the end (T1), the IG showed a significant increase in the mean score (9.30 ± 2.89), while the CG maintained values similar to T0 (4.60 ± 2.41) (Table1). The difference within groups was highly significant (p